Ways To Develop Infrastructure of Tourism Destinations - Bakhodir Turayev; Ulugbek Atamurodov (Procedia of Social Sciences and Humanities, 2021)
This article explores the theoretical aspects of coordinating the management of infrastructure components in the development of tourism destinations and the practical state of the infrastructure in destinations. Based on the analysis, proposals have been developed based on international experience in the development of tourism infrastructure.